Adapting to a new home: resettlement and mental health service experiences of immigrant and refugee youth in Montreal - Charles Gyan; Farhin Chowdhury; Ata Senior Yeboah (Humanities & Social Sciences Communications, 2023)
Abstract Resettlement and mental health services are critical support systems for refugee and immigrant youth (RIY) as they navigate the complexities of settling into their new homes. These services play a vital role in meeting the needs of RIY and helping them feel welcomed into Canadian society. The purpose of this study is to provide insight into RIY’s experiences with resettlement and mental health service providers in Montreal, Canada. Adopting a descriptive quantitative research approach, this study utilized online surveys to gather data. The findings indicate that cultural and linguistic barriers are the major obstacles faced by refugee and immigrant youth when accessing resettlement and mental health services in Montreal. Protective resources, such as family, friends, and ethnic communities, were identified as important facilitators of successful integration into Canadian society. To improve services, cultural sensitivity should be a priority for providers, as recommended by this study. By acknowledging the significance of cultural barriers in accessing resettlement and mental health services, this study emphasizes the need for service providers to prioritize cultural sensitivity in their efforts to improve services.